Bipartite containment disturbance rejection using disturbance observers - Wu, Jie; Wang, Li; Zhan, Xisheng (IEEE access, 2022)
This paper mainly addresses bipartite containment control of multi-agent systems (MASs) subject to exogenous disturbances. With dynamic gain technique independent of any global information, the disturbance observer method is applied to estimate disturbances generated by heterogeneous nonlinear exosystems. Two disturbance observer-based controllers are accordingly presented via state feedback approach and output feedback approach. By means of appropriate Lyapunov method, it is shown that the bipartite containment control is realized under sufficient criteria. Finally, simulations are employed to validate the effectiveness and correctness of our proposed controllers.